SISOM inhibits seed germination by regulating the expression of ABA/GA metabolic genes and SIABI5 in Solanum lycopersicum - Xiao-chun SUN; Yong-feng GAO; Ning ZHANG; Hui-rong LI; Shu-zhang YANG; Yong-sheng LIU (Journal of Integrative Agriculture, 2015)
SOM encodes a nucleus-localized CCCH-type zinc finger protein and negatively regulates seed germination in Arabidopsis thaliana. We have previously demonstrated that ectopic expression of SIABI3, an important transcription factor in abscisic acid (ABA) signaling pathway, resulted in alteration of SISOM expression patterns in both leaf and seed of tomato. In this study, we aimed to elucidate the function of tomato SISOM in regarding to seed germination and seedling development. Here, we constructed SISOM over-expression vector pBI121-SOM driven by CaMV 35S promoter, and the recombinant plasmid was incorporated into wild-type tomato by the method of Agrobacterium tumefaciens-mediated transformation. The result showed that over-expression of SISOM conferred enhanced responses to exogenous ABA application during seed germination and seedling development. In addition, ectopic expression of SISOM resulted in the alteration of expression level of ABA/GA (gibberellins) metabolic genes, such as SIABA1, SlCYP707A1, SlGA3ox2, and SIGA2ox4, in both leaf and seed. The ABA anabolic gene SIABA1 and the GA catabolic gene SIGA2ox4 were up-regulated while the ABA catabolic gene SICYP707A1 and the GA anabolic gene SIGA3ox2 were down-regulated. Compared to wild type, the expression level of SIABI5 was increased by about 40–50% in transgenic seeds while adding exogenous ABA treatment. These results support the notion that SISOM inhibits seed germination by regulating ABA/GA metabolic genes and SIABI5 expression in Solanum lycopersicum.